PENERAPAN METODE PEMBELAJARAN PREVIEW, QUESTION, READ, SUMMARIZE, TEST (PQRST) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA PADA PEMBELAJARAN TEMATIK KELAS V DI MADRASAH IBTIDAIYAH AL-MUNAWWARAH KOTA JAMBI - M Asyraf; Indriyani; Ugi Nugraha; Urip Sulistiyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This thesis discusses the application of the Preview Question Learning Method in Improving Reading Comprehension Skills for Class V Students in Thematic Learning at Madrasah Ibtidayah Al-Munawwarah Jambi City. This research focuses on the thematic learning process using the preview question learning method. This study uses a classroom action research approach. Data collection techniques through interviews, observation, and documentation. Data analysis used descriptive analysis.In planning the teacher makes lesson plans, syllabus and prota and promissory notes according to existing provisions. The implementation of thematic learning is carried out in two cycles. Each cycle consists of two meetings and an evaluation of learning using the 2013 curriculum assessment with three aspects or domains assessed, namely knowledge, attitudes and skills. At the beginning of the observation, the researcher found that students' reading skills were still low. Because teachers still use conventional methods (lecture methods) and have not used appropriate learning strategies. This makes students feel bored with the learning process in class. Thus, it can be concluded that the use of the preview question learning method can improve students' reading comprehension skills in thematic learning at Madrasah Ibtidaiyah Al-Munawwarah Jambi City.